Significance of the Vascular Concentration of Angiotensin II-Receptor Blockers on the Mechanism of Lowering Blood Pressure in Spontaneously Hypertensive Rats - Shinji Takai; Denan Jin; Hiroshi Sakonjo; Takayuki Takubo; Toyofumi Nakanishi (Elsevier, 2013)
To clarify the hypotensive mechanism of angiotensin II receptor-blockers (ARBs), drug concentrations in plasma and vascular tissues were measured using matrix-assisted laser desorption ionization time-of-flight mass spectrometry and imaging mass spectrometry. In spontaneously hypertensive rats, systolic blood pressure (SBP) was measured 2 and 24 h after administration of candesartan cilexetil (0.3, 1, or 3 mg/kg) or azilsartan (0.3, 1, or 3 mg/kg). SBP was similarly lowered 2 h after administration of azilsartan or candesartan cilexetil, but it was significantly lower in the azilsartan-treated group than in the candesartan cilexetil-treated group at 24 h. Angiotensin II-induced vascular contractions were similarly attenuated 2 h after administration of these drugs, and the contractions were significantly lower in the azilsartan-treated group at 24 h. Although plasma concentration was significantly lower in the azilsartan-treated group at 24 h, vascular concentration of azilsartan was significantly greater than that of candesartan. Significant correlations between SBP and vascular concentrations were observed both at 2 and 24 h, while no significant correlation was observed between plasma and vascular concentrations. In conclusion, the mechanism of ARB-induced hypotension is likely to depend on vascular concentrations rather than plasma concentrations. Keywords:: angiotensin II, angiotensin II receptor blocker, hypertension, imaging mass spectrometry, vascular contraction